Optimization of VSV‐ΔG‐spike production process with the Ambr15 system for a SARS‐COV‐2 vaccine. Issue 7 (31st March 2022) - Rosen, Osnat; Jayson, Avital; Goldvaser, Michael; Dor, Eyal; Monash, Arik; Levin, Lilach; Cherry, Lilach; Lupu, Edith; Natan, Niva; Girshengorn, Meni; Epstein, Eyal
Abstract: To face the coronavirus disease 2019 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus, our institute has developed the rVSV‐ΔG‐spike vaccine, in which the glycoprotein of vesicular stomatitis virus (VSV) was replaced by the spike protein of SARS‐CoV‐2. Many process parameters can influence production yield. To maximize virus vaccine yield, each parameter should be tested independently and in combination with others. Here, we report the optimization of the production of the VSV‐ΔG‐spike vaccine in Vero cells using the Ambr15 system. This system facilitates high‐throughput screening of process parameters, as it contains 24 individually controlled, single‐use stirred‐tank minireactors. During optimization, critical parameters were tested. Those parameters included: cell densities; the multiplicity of infection; virus production temperature; medium addition and medium exchange; and supplementation of glucose in the virus production step. Virus production temperature, medium addition, and medium exchange were all found to significantly influence the yield. The optimized parameters were tested in the BioBLU 5p bioreactors production process and those that were found to contribute to the vaccine yield were integrated into the final process. The findings of this study demonstrate that an Ambr15 system is an effective tool for bioprocess optimization of vaccine production using macrocarriers and that the combination of production temperature, rate of medium addition, and medium exchange significantly improved virus yield. Abstract : Rosen et al. report the optimization of the VSV‐ΔG‐spike vaccine production process in Vero cells using the Ambr15 system. Many process parameters can influence production yield and during optimization, many critical parameters were tested. The findings of this study demonstrate that an Ambr15 system is an effective tool for bioprocess optimization of vaccine production using macrocarriers and that the combination of production temperature, rate of medium addition, and medium exchange significantly improved virus yield. Moreover, the optimized parameters were subsequently tested in the BioBLU 5p vaccine bioreactors production process and most were found to have the same useful effects and were, therefore, integrated into the final production process.